Doctoral Research in Rural Education and the Rural R & D Menu - Hobart L. Harmon; Craig B. Howley; John R. Sanders (Journal of Research in Rural Education, 1996)
We analyzed abstracts of 196 doctoraldissertations completed during 1989-1993, using The Rural Education Research and Development Menu developed jointly by the Appalachia Educational Laboratory and members ofthe rural education special interest group ofthe American Educational Research Association. Categories from the menu were used to categorize issues investigated by the dissertations. Overall school effectiveness was the topic to which dissertations were most frequently assigned, whereas the se of(advanced electronic)technology in rural schools was the topic to which dissertations were least frequently assigned. Implications for researchers and practitioners are offered.